Form and transformation : a study in the philosophy of Plotinus - Schroeder, Frederic Maxwell, 1937- (McGill-Queen's studies in the history of ideas, 1992)
The Platonic Form is often presented as an instrument of explanation and as a cause in ontology, epistemology, and ethics. As such, it is usually approached from the perspective of its relations to the particulars of the sensible world. Frederic Schroeder contends that Plotinus argues for the sovereignty of the Platonic Form both as a ground of being and as an intrinsically valuable object of intellective and spiritual vision. These two aspects coalesce in the thought of Plotinus, for whom the Form is, apart from its philosophical uses, an object of enjoyment. Schroeder argues also that the particular must be seen as having an intrinsic character, distinct from its relationship to the Form or to other particulars. The particular thus becomes a window on the world of Form. In the course of his exploration of the sovereignty of Form, Schroeder examines the themes of illumination, silence, language, and love. He undertakes an immanent interpretation of the Plotinian text, showing how Plotinian vocabulary displays intricate internal connections and genetic relationships. Schroeder shows that Plotinus' thought is not susceptible to organization into a closed, linear synthesis but has its own order, centred on the conviction that Form is of intrinsic value and that it is only from the perspective of this intrinsic value that we can understand its uses and significance in explanation and causation. Rather than trying to construct such a synthesis, Schroeder, starting from this basic insight into Plotinus' understanding of the Platonic Form, leads the reader to a greater understanding of Plotinus' manner of philosophizing.